Safety and Efficacy of Intravenous Colistin in Neonates With Culture Proven Sepsis - Serafettin Tekgunduz, Kadir (Iran J Pediatr, 2015)
BACKGROUND: Although it is well described among adults, intravenous colistin use and its associated toxicities in newborns are poorly understood. OBJECTIVES: We present our experience of efficacy and safety of intravenous colistin in the treatment of sepsis in term and preterm neonates. PATIENTS AND METHODS: The records of neonates who received colistin between January 2013 and February 2014 were retrospectively reviewed. All neonates with culture proven nosocomial infections due to multidrug resistant organisms and treated continuously with colistin for more than 72 hours were included in the study. RESULTS: Patients were evaluated for clinical and microbiological response to the drug and its and side effects. Twelve newborn infants with mean 31.8 ± 3.5 weeks gestational age and median 1482 (810 - 3200) gram birth weight were included. 11/12 (91.7%) patients showed microbiological clearance with intravenous colistin. One patient who had recurrent cerebrospinal fluid positive culture was treated with intraventricular colistin. The major side effects observed was hyponatremia and hypokalemia in 2 (16.6%) patients, all infants required magnesium supplementation. CONCLUSIONS: Intravenous colistin administration appears to be safe and efficacious for multidrug-resistant gram-negative infections in neonates, including preterm infants. However, we believe that large prospective controlled studies are needed to confirm its efficacy and safety in neonates.